1995
DOI: 10.1177/074823379501100303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lung Permeability Correlate With Lung Histology in a Chronic Exposure Model

Abstract: In a simulated military flight-line exposure protocol, the effects of JP-8 jet fuel exposure on lung epithelial permeability were evaluated in male Fischer 344 rats (F344). Exposures were nose-only and for one hour daily. Groups were exposed for 7, 28, and 56 days. A protocol for administering a low dose (500mg/m3/hr) and a high dose (813-1094mg/m3/hr) of JP-8 jet fuel was used. Longitudinal sham-exposure groups (no jet fuel) for 7, 28, and 56 days were included in the protocol. Lung epithelial permeability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 6 publications
2
50
2
Order By: Relevance
“…Histological analysis can also provide information about morphological changes to tissue that indicate stress and injury. This type of analysis was used to demonstrate injury to tissues that directly contact JP-8 fuel such as lung and skin (Hays et al, 1995;Robledo et al, 2000;Gallucci et al, 2004). However, little information is available concerning the systemic toxicity of JP-8 through the evaluation of tissue injury with histological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Histological analysis can also provide information about morphological changes to tissue that indicate stress and injury. This type of analysis was used to demonstrate injury to tissues that directly contact JP-8 fuel such as lung and skin (Hays et al, 1995;Robledo et al, 2000;Gallucci et al, 2004). However, little information is available concerning the systemic toxicity of JP-8 through the evaluation of tissue injury with histological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological evaluation after acute JP-8 aerosol exposures showed lesions following a range of doses up to 113 mg/m 3 (4,17,19). Subsequent in vitro experiments in our labs explored the role of epithelial barrier function upon JP-8 exposure.…”
Section: Morphological Evaluation-histology and Micrographymentioning
confidence: 99%
“…Initial in vivo experiments in our labs revealed that aerosol exposure results in the targeting of distal airways as shown by enhanced respiratory permeability to 99m TcDTPA (4,17,18). Morphological evaluation after acute JP-8 aerosol exposures showed lesions following a range of doses up to 113 mg/m 3 (4,17,19).…”
Section: Morphological Evaluation-histology and Micrographymentioning
confidence: 99%
“…Furthermore, no coal ash particles solubility in UPW has been determined. (Hays et al, 1995) has previously determined that increased clearance of 99m Tc-DTPA correlates with increased pathological injury. Furthermore, (Witten et al, 1985) has demonstrated that pulmonary clearance of 99m Tc-DTPA is an extremely sensitive marker of lung injury.…”
Section: Characteristics Of Re-suspended Ash Particlesmentioning
confidence: 99%